Registros del carbón de la panoja Sporisorium reilianumen maíces de Córdoba y San Luis, Argentina - Torrico Ramallo, Ada Karina; Barontini, Javier Miguel; Ruiz Posse, Agustina María; Gimenez, Maria De La Paz (Asociación Argentina de Fitopatólogos, 2022)
Poster